The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c4nr04089a
|View full text |Cite
|
Sign up to set email alerts
|

Sub-10 nm transparent all-around-gated ambipolar ionic field effect transistor

Abstract: A versatile ionic field effect transistor (IFET) which has an ambipolar function for manipulating molecules regardless of their polarity was developed for the operation at a wide range of electrolytic concentrations (10−5 M–1 M).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…Recently, the nanofluidic field effect transistor (FET) [20][21][22], comprising a gate electrode embedded beneath the thin dielectric channel layer, has been developed. It has been demonstrated that the FET is capable of actively controlling the surface charge property and ionic conductance in a solid-state nanochannel and nanopore by controlling the gate voltage applied to the gate electrode 4 [23][24][25][26][27][28][29][30][31][32][33][34]. Compared to the large number of studies on the solid-state nanofluidic FET, Benson et al [35] and Milne et al [36] recently initiated the studies of the FET control of the Donnan potential, the electrical potential at the PE layer/solid channel interface [37], and the electrokinetic flow (EKF) in the functionalized soft nanochannels.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the nanofluidic field effect transistor (FET) [20][21][22], comprising a gate electrode embedded beneath the thin dielectric channel layer, has been developed. It has been demonstrated that the FET is capable of actively controlling the surface charge property and ionic conductance in a solid-state nanochannel and nanopore by controlling the gate voltage applied to the gate electrode 4 [23][24][25][26][27][28][29][30][31][32][33][34]. Compared to the large number of studies on the solid-state nanofluidic FET, Benson et al [35] and Milne et al [36] recently initiated the studies of the FET control of the Donnan potential, the electrical potential at the PE layer/solid channel interface [37], and the electrokinetic flow (EKF) in the functionalized soft nanochannels.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Elucidating the fundamentals of ion transportation also remains an active research area because various related phenomena are not fully understood yet. Ion concentration polarization (ICP) is a representative phenomenon of such novel ion transport in a nanoscale fluidic device, usually driven by an external electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Typical behaviour is that the ion concentration becomes extremely low at an anodic side (referred to as an ion-depletion zone) and enriches at a cathodic side (referred to as an ion-enrichment zone) in the case of a cation-selective membrane. Although the mechanism involves complex interactions of electric fields and electrokinetic flows 35 36 37 , the eye-catching fact in terms of engineering applications is that ICP can play as an electrical filter. This virtual barrier rejects the entrance of charged species into the ion-depletion zone, so that it can be utilized as a water desalination/purification mechanism 2 38 and a biomolecular preconcentration mechanism 24 25 .…”
Section: Resultsmentioning
confidence: 99%